The Self-Esteem of Black Women in America: The Contribution to bell hooks: Examining the Impact of Historical Accounts and Societal Stereotypes on the Self-Esteem of Black Women (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present paper attempts to explore and analyse the self-esteem of black women in Americathrough the writings of American black feminist bell hooks. It also looks at the historical accounts thatbecame responsible for the lack of self-esteem in American black women. It throws light upon thenegative portrayals of black women and societal stereotypes leading to their trauma and violenceexperiences.